Use of teletransmission and influence of telemedicine on enhancing healthcare quality in opinions of paramedics from the Podkarpackie Province - a pilot survey - Burdzy, Danuta; Ozga, Dorota; Kosydar-Bochenek, Justyna; Migut, Małgorzata; Burdzy, Kamil; Lewandowski, Bogumił (Journal of Education, Health and Sport, 2017)
Foreword. The paper presents new solutions in approach to telemedicine related to the development and implementation of advanced technologies. In the coming years, it is expected that technologies such as 3D imaging, telemedicine, etc., will contribute to enhancing the quality of medical care and allow faster and cheaper management of patients. Aim. Evaluating the operation of the teletransmission system used by emergency medical services (ZRM) and its impact on the enhancement of medical care quality. Material and methods. The survey was carried out on 50 persons employed in the emergency medical services system (PRM system) within the Podkarpackie Province. The method of diagnostic survey was employed. A questionnaire was designed in order to collect information necessary to meet the research purpose of this work. The questionnaire consists of questions regarding various views, health-related behaviours, and respondents’ knowledge and awareness of ICT (information and communication technology) solutions in medicine. Results. Among 50 surveyed persons, there were 30 paramedics (60%), 11 PRM nurses (PRM: emergency medical services) (22%), 8 PRM doctors (16%), and a doctor of medicine (2%). 10 of the surveyed persons were women (20%) while 40 were men (a majority of 80%). As far as age groups are concerned, 5 persons (10%) were below 25, 17 persons (34%) were between 26 and 35, 25 persons (50%) were between 36 and 45, and 3 persons (6%) were over 46 years of age. All participants work for hospital emergency wards in the Podkarpackie Province. The survey has proven that the idea of the innovative patient care based on telemedicine is strongly supported by the respondents. Conclusions. In the opinion of the PRM personnel, the system operates efficiently. Teletransmission is used by the emergency medical services as a diagnostic tool and allows one to improve procedures and provides help in taking decisions related to managing patients with ACS. It contributes to enhancing quality of medical care and patient comfort. This is also a high potential area.